Flood Pulse and Aquatic Habitat Dynamics of The Sentarum Floodplain Lakes Area - Hidayat Hidayat; Siti Aisyah; Riky Kurniawan; Iwan Ridwansyah; Octavianto Samir; Gadis Sri Haryani (Indonesian Society of Limnology, 2020)
The Lake Sentarum is a complex of floodplain lakes in the middle part of the Kapuas River system in West Kalimantan, Indonesia. The area has a great ecological and economic importance, however, the Sentarum lakes complex and its catchment area are generally threatened by deforestation, fire, monoculture agroindustry, and pollution.The objective of this research is to establish the hydrological characteristics of the Sentarum lakes area and to reveal the dynamics of aquatic habitat resulted from changing water levels. Data were collected during our field campaigns of 2013-2017 representing the seasons. The water level was measured using a pressure sensor placed at the Lake Sentarum National Park resort, while rainfall data were obtained from the data portal of the Tropical Rainfall Measuring Mission. Inundation monitoring was carried out using a time-lapse camera. A hydrological model is used to simulate water levels beyond measurement period. Water quality and fish sampling were carried out at the lake area. Vegetation observation was carried out at the selected riparian zone of the lake area using the line transect method. Water level records show that the Sentarum floodplain lakes have two peaks of inundation period following the bimodal pattern of rainfall in the equatorial Kapuas catchment. This water level dynamics induced changes in water quality, nutrient availability, vegetation cover, and fish diversity found in the Sentarum lakes area. Despite its seasonal changes, water quality of Sentarum lakes is generally good and suitable for aquatic biota. Fish diversity of the Sentarum lakes is relatively higher during high water periods.